2021
DOI: 10.28918/erudita.v1i1.4401
|View full text |Cite
|
Sign up to set email alerts
|

Students' attitude and difficulties in practicing speaking through autonomous learning on podcast

Abstract: This research aims to examine the students' attitude on producing podcasts as a media to practice speaking for autonomous learning and the difficulties faced by students in producing podcast of speaking. This research was descriptive qualitative research and the data is collected using questionnaire and semi-structured interview. As many 28 students of English Education Department of one of public Islamic institution in Central Java in various semesters participated in the questionnaire and 4 students were cho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…In addition to referring to existing HNC resources and peer support groups, our study identified novel ways to meet the needs of patients, carers and healthcare professionals through the development of a series of 5‐min podcasts presented by patients, carers and healthcare professionals prior to the commencement of treatment, throughout treatment and extending into the survivorship period at 1 and 5 years posttreatment completion. Podcasts are recognised as an emerging form of education and teaching, allowing users to pause, rewind and relisten to information at their own pace 30 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to referring to existing HNC resources and peer support groups, our study identified novel ways to meet the needs of patients, carers and healthcare professionals through the development of a series of 5‐min podcasts presented by patients, carers and healthcare professionals prior to the commencement of treatment, throughout treatment and extending into the survivorship period at 1 and 5 years posttreatment completion. Podcasts are recognised as an emerging form of education and teaching, allowing users to pause, rewind and relisten to information at their own pace 30 …”
Section: Discussionmentioning
confidence: 99%
“…Podcasts are recognised as an emerging form of education and teaching, allowing users to pause, rewind and relisten to information at their own pace. 30 Although the EBCD toolkit was an invaluable resource, we found it challenging at times to work out the best way to apply the resources available in the toolkit in each workshop. Being able to refer to EBCD examples provided as case studies was helpful to understand how workshops were run in previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…At present, the development of technology in the world of education is the most essential thing teachers do to provide memorable teaching that can encourage students to be actively involved in learning activities. In language learning, technology offers ease of access to learning which promotes learners to have self-regulated learning (Buana & Miftachudin, 2021). Thus, the existing technology is increasingly varied and innovative, and almost everyone has a technological device in their daily life.…”
Section: Introductionmentioning
confidence: 99%